2014
DOI: 10.1007/s10964-014-0149-0
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Characteristics, Body Mass Index, and Risk for Hypertension in Young Adolescents

Abstract: Inadequate sleep has been identified as a risk factor for a variety of health consequences. For example, short sleep durations and daytime sleepiness, an indicator of insufficient sleep and/or poor sleep quality, have been identified as risk factors for hypertension in the adult population. However, less evidence exists regarding whether these relationships hold within child and early adolescent samples and what factors mediate the relationship between sleep and risk for hypertension. Using data from the Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 72 publications
1
32
0
4
Order By: Relevance
“…The quality of evidence was rated as high for the randomized trials. Among the 11 longitudinal studies, 8 reported that longer sleep was associated with better emotional regulation at follow-up (Barlett et al 2012;Fredriksen et al 2004;Kalak et al 2014;Lin and Yi 2015;Lumeng et al 2007;Pasch et al 2012;Roberts and Duong 2014;Roberts et al 2009) while 3 reported no association (Asarnow et al 2014;Chang and Gable 2013;Silva et al 2011). Given that only 1 study used an objective assessment of sleep duration (Silva et al 2011), the quality of evidence was downgraded from low to very low (serious risk of bias).…”
Section: Emotional Regulationmentioning
confidence: 99%
See 3 more Smart Citations
“…The quality of evidence was rated as high for the randomized trials. Among the 11 longitudinal studies, 8 reported that longer sleep was associated with better emotional regulation at follow-up (Barlett et al 2012;Fredriksen et al 2004;Kalak et al 2014;Lin and Yi 2015;Lumeng et al 2007;Pasch et al 2012;Roberts and Duong 2014;Roberts et al 2009) while 3 reported no association (Asarnow et al 2014;Chang and Gable 2013;Silva et al 2011). Given that only 1 study used an objective assessment of sleep duration (Silva et al 2011), the quality of evidence was downgraded from low to very low (serious risk of bias).…”
Section: Emotional Regulationmentioning
confidence: 99%
“…b Includes 11 longitudinal studies (Asarnow et al 2014;Barlett et al 2012;Chang and Gable 2013;Fredriksen et al 2004;Kalak et al 2014;Lin and Yi 2015;Lumeng et al 2007;Pasch et al 2012;Roberts and Duong 2014;Roberts et al 2009;Silva et al 2011).…”
Section: Harms/injuriesmentioning
confidence: 99%
See 2 more Smart Citations
“…First, Peach et al (2015) examined body mass index (BMI) as a possible mediator of the association between sleep problems and hypertension risk in a sample of sixth grade students (ages 11-13 years). Interestingly, sex-specific patterns emerged: whereas school-night sleep duration, weekend night sleep duration, and daytime sleepiness were each associated with boys' BMI which was in turn associated with hypertension risk; only daytime sleepiness was associated with girls' BMI and had a significant indirect effect on hypertension risk.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 99%